О методике частичной ампутации кисти у птиц - Осинский, Л.П.; Таран, В.С. (Вестник зоологии, 1978)
The method of X-ray contrast mass injection to arterial vessels with subsequent angiography was used to study a general scheme and some species peculiarities of arteries branching in the antebrachium and hand regions in various birds. The ligature is applied to main arteries of the antebrachium and a part of the metacarpus with the 3d finger is separated. This amputation of a part of the hand does not affect noticeably the birth general appearance.